Answer:
a) 456.48m
b) 3343.91m
c) - 76.376m
Total displacement = 3724.01m
Step-by-step explanation:
Using kinematic equation for displacement
◇x1 = Vo t + 1/2 at^2
Where ◇x1 = displacement
Vo = initial velocity
a = acceleration
t = time
◇x1 = 0(15.3) + 1/2 (3.9)(15.3)^2
◇x1 = 0 + 456.48
Displacement = 456.48m
b) ◇x2 = Vt1
V = velocity = 59.67m/s
◇x2 = 59.67 ×0.934minute×60seconds
◇x2 = 59.67 ×56.04 = 3343.91
c)
a= -11.1m/s
= (-11.1 m/s^2× 3.71seconds)
◇ x3 =1/2 (41.18m/s ×3.71)
◇x3 =- 76.376m
Total displacement = ◇x1 + ◇x2 + ◇x3
Total displacement = 456.48 + 3343.91 - 76.376
Total displacement = 3724.01m